Protokoly Pervoj Obščepartijnoj Konferencii Partii Socialistov-Revoljucionerov, Avgust 1908 = proceedings of the First All-Party Conference of the Socialist-Revolutionary Party, August 1908 (Kraus, 1984)
Photomechanical repr. : Paris : CK P.S.-R., 1908. - Bibl., index.